Figure 5 in A revision of Nereimyra (Psamathini, Hesionidae, Aciculata, Annelida) - Pleijel, Fredrik; Rouse, Greg W.; Nygren, Arne (Zenodo, 2011)
Figure 5. Nereimyra aphroditoides, dorsal view of live relaxed specimens. A, neotype, Disko Fjord, Greenland. B, anterior end from Svalbard. Scale bar: A = 1 mm; B, scale unknown. : Published as part of Pleijel, Fredrik, Rouse, Greg W. & Nygren, Arne, 2012, A revision of Nereimyra (Psamathini, Hesionidae, Aciculata, Annelida), pp. 36-51 in Zoological Journal of the Linnean Society 164 (1) on page 45, DOI: 10.1111/j.1096-3642.2011.00756.x, http://zenodo.org/record/4720224